The First Record of Zinowiewia in the Brazilian Flora and a Short Account of Its History - Biral, Leonardo [UNESP]; Lombardi, Julio Antonio [UNESP] (Harvard University Botany Libraries, 2017)
We report here the first record of Zinowiewia (Celastraceae) for the Brazilian flora, based on a specimen of Z. australis collected in Serra do Surucutus, at 1000-1400 m, Roraima state, in the basin of the Rio Branco and subsequently the Rio Negro, the latter being the largest tributary of the Amazon River. This novelty will be added to the Brazilian Flora 2020 project. With this addition, the family is now represented in Brazil by 20 genera and 142 species. An account of the history of Zinowiewia is also provided.
Keywords: Brazil; Celastraceae; Celastroideae; Lundell; Wimmeria